Method for suppressing adhesion and growth of clinker in boiler furnace in co-firing multiple types of solid fuels with pulverized coal combustion boiler

By analyzing clinker properties and adjusting fuel blends in pulverized coal boilers, clinker adhesion and growth are suppressed, ensuring stable operation and preventing operational disruptions.

JP2025007645APending Publication Date: 2025-01-17TOSOH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023109183
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing methods fail to effectively prevent clinker adhesion and growth inside pulverized coal combustion boilers when co-firing solid fuels with varying ash properties, leading to operational disruptions and inefficiencies.

Method used

Analyze the crystalline state of clinker discharged from the boiler bottom using XRD, evaluate adhesion growth properties, and adjust the type and blending ratio of solid fuels to suppress clinker growth by controlling ash composition and formation temperature.

Benefits of technology

Enables stable and continuous operation of pulverized coal combustion boilers by timely detection and prevention of clinker adhesion, avoiding emergency shutdowns and maintaining efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007645000001_ABST
    Figure 2025007645000001_ABST
Patent Text Reader

Abstract

To provide a method for maintaining and continuing stable operation of a boiler by taking appropriate measures without stopping the boiler while checking clinker adhesion status in a pulverized coal combustion boiler, assuming a case of co-firing solid fuels such as biomass solid fuels having ash properties significantly different from conventional coal.SOLUTION: When multiple types of solid fuels are burned in a pulverized coal combustion boiler, a crystal state of clinker discharged from a furnace bottom part of the boiler is analyzed to evaluate adhesion and growth properties of the clinker, and then the types and mixing ratio of the solid fuels to be co-fired are adjusted.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for co-firing multiple types of solid fuels in a pulverized coal combustion boiler at a coal-fired power plant, and provides a method for promoting reduction in CO2 emissions by increasing the usage rate of biomass solid fuel in pulverized coal combustion boilers at existing coal-fired power plants and reducing the use of coal when burning a wide variety of solid fuels of different qualities, such as biomass solid fuel, which is one type of renewable energy that is effective in reducing CO2, and coal from different origins, in a pulverized coal combustion boiler, thereby suppressing the adhesion and growth of clinker on the furnace walls and achieving stable and continuous operation. [Background technology]

[0002] In recent years, global warming due to the increase in atmospheric CO2 concentration has become evident, and reducing the use of fossil fuels that increase atmospheric CO2 concentration has become an issue. In particular, coal-fired power generation uses coal that emits a lot of CO2, so it is a power generation method that requires measures to reduce CO2 emissions. In contrast to conventional subcritical or supercritical pressure power generation (power generation efficiency of about 38%) in which coal is pulverized and burned, advanced technologies that increase power generation efficiency and reduce CO2 emissions, such as advanced ultra-supercritical pressure power generation (power generation efficiency of about 46%), coal gasification combined cycle power generation (power generation efficiency of about 46%), and coal gasification fuel cell combined cycle power generation (power generation efficiency of about 55%), have been introduced to put into practical use.

[0003] On the other hand, pulverized coal-fired boilers in conventional subcritical or supercritical pressure power generation, for example in the case of private power generation facilities of chemical companies, efficiently supply both heat and electricity required for chemical processes at the same time, and as such have an energy efficiency of over 50% as a thermal power plant boiler. If we could switch even a part of the main fuel, coal, to solid fuels such as biomass solid fuels, which are effective in reducing CO2 emissions, and increase their usage rate, we could reduce CO2 emissions without introducing expensive equipment that employs highly advanced technologies. However, biomass solid fuels have properties that are significantly different from coal, so there are many challenges to simply switching from coal.

[0004] Pulverized coal combustion boilers, which are widely used in conventional coal-fired power plants, generally mainly comprise a burner, a furnace, heat transfer tubes, and a chimney. Solid fuel blown in together with air is burned in the furnace by the burner, and heat exchange is performed by a number of heat transfer tubes (evaporator tubes) arranged in the furnace. The feedwater supplied to the evaporator tube is heated and pressurized by this heat exchange, generating steam. The combustion gas generated by combustion is discharged from the chimney.

[0005] In such pulverized coal-fired boilers, coal that has been crushed and pulverized to burn efficiently is used as solid fuel, but when woody biomass or plant-based biomass, which are common as biomass solid fuels, such as construction waste or white pellets that contain a lot of plant fiber, are used, there is a limit to their mass co-firing with coal because they have poor crushability as is. Therefore, semi-carbonized products and biomass solid fuels called black pellets, which are made by heat-treating woody biomass in an oxygen-poor environment to partially decompose the plant fiber and improve crushability, are beginning to be used in pulverized coal-fired boilers as alternative fuels to coal.

[0006] In pulverized coal-fired boilers, when some of the ash contained in the fuel adheres to the furnace walls and the surface of the evaporator tubes, a deposit called clinker grows. When clinker adheres and grows, not only does it reduce the efficiency of the boiler, but it also makes it more likely that a large amount of clinker will fall at once, causing the seal water at the bottom of the furnace to evaporate all at once, causing a sudden rise in furnace pressure and other problems that activate the interlock.

[0007] Since the amount and characteristics of ash in coal vary depending on the place of origin, the state of clinker that adheres to the surface of the boiler furnace wall and evaporator tube changes depending on the coal used, and it is known that there are coals that are easy to use and coals that are difficult to use. In addition, it is known that the amount and characteristics of ash in biomass fuels are significantly different from coal, and the adhesion characteristics to the surface of the furnace wall and evaporator tube change further. Therefore, various boiler operating methods have been proposed to predict and evaluate the adhesion of ash or to prevent the adhesion of ash.

[0008] Japanese Patent Application Laid-Open No. 2004-361368 proposes a method in which coal is first converted to coal ash to obtain coal ash, and this coal ash is sintered at multiple temperatures within the combustion temperature range of a boiler to obtain sintered ash at each heating temperature, the weight of each sintered ash obtained is measured and placed into a cylindrical wire mesh of a Rattler testing machine, the wire mesh is rotated at a constant rotation speed for a constant number of rotations to remove particles separated from the sintered ash through the mesh, the weight of the sintered ash remaining in the wire mesh is measured, the degree of adhesion is measured from the ratio obtained by dividing the weight of the sintered ash after the test by the weight of the sintered ash before the test, and the adhesion of ash to heat transfer tubes in an actual boiler is predicted and evaluated from the measured degree of adhesion of the ash.

[0009] In addition, JP 2017-190908 A proposes a boiler operation method in which the mixing ratio of multiple types of solid fuels is determined based on the ash content in the solid fuel and the mullite content in the ash.

[0010] All of these methods involve analyzing solid fuels in advance and determining the mixing ratio of multiple types of solid fuels based on the results, but even when these methods are used, it is actually not possible to completely prevent clinker adhesion inside the boiler, and even if the fuel blend is the same, the clinker adhesion state inside the boiler changes due to variations and fluctuations in fuel quality and in-furnace combustion conditions, and the risk of trouble occurring due to the growth of clinker adhesion inside the boiler cannot be eliminated. Furthermore, when there are signs of the growth of adhering clinker inside the boiler, it is unavoidable to apply an external impact to the clinker while the adhesion is still minor, to peel it off, or to adjust the fuel blend. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2004-361368 A [Patent Document 2] JP 2017-190908 A Summary of the Invention [Problem to be solved by the invention]

[0012] The present invention has been made in consideration of the above problems, and its purpose is to provide a method for maintaining and continuing stable operation of a boiler by assuming a case in which a solid fuel, such as a biomass solid fuel, whose ash properties are significantly different from those of conventional coal, is mixed and burned, and by checking the state of clinker adhesion inside the boiler and taking appropriate measures without stopping the boiler. [Means for solving the problem]

[0013] As a result of intensive research by the inventors to solve the above-mentioned problems, they discovered that when multiple types of solid fuels with different heating values, ash contents, compositions contained in the ash, etc. are burned in a pulverized coal-fired boiler, the clinker (hereinafter sometimes referred to as "bottom ash clinker") discharged from the bottom of the furnace of the operating pulverized coal-fired boiler can be collected and analyzed, the adhesion and growth properties of the clinker can be evaluated, and then the types and blending ratio of the solid fuels to be mixed and burned can be adjusted, thereby making it possible to maintain continuous operation of the pulverized coal-fired boiler without shutting it down, which led to the completion of the present invention.

[0014] That is, the present disclosure has the following gist.

[0015] [1] A method for suppressing the deposition and growth of clinker in a boiler furnace, when multiple types of solid fuels are burned in a pulverized coal-fired boiler, by analyzing the crystal state of the clinker discharged from the bottom of the boiler furnace, evaluating the deposition and growth tendency of the clinker, and then adjusting the types and mixing ratio of the solid fuels to be mixed.

[0016] [2] The method according to [1] above, characterized in that the clinker discharged from the bottom of a pulverized coal-fired boiler furnace is detached from the inner wall of the boiler furnace and falls.

[0017] [3] The method according to [1] or [2] above, characterized in that the clinker discharged from the bottom of a pulverized coal-fired boiler furnace is peeled off from the inner wall of the boiler furnace by applying an external impact and dropped to the bottom of the boiler furnace.

[0018] [4] The method according to any one of [1] to [3] above, characterized in that, in a diffraction pattern obtained by subjecting clinker discharged from the bottom of a pulverized coal-fired boiler to XRD measurement in the region of 2θ=15 to 50°, the amount of amorphous matter is defined as the area of ​​the halo region above the line connecting the base points of 2θ=15° and 2θ=50°, and the sum of the areas of the diffraction peaks detected above the halo region is defined as the amount of crystalline matter, and the ratio of the amount of amorphous matter to the sum of the amount of amorphous matter and the amount of crystalline matter is defined as the amorphous proportion of the clinker.

[0019] [5] Using multiple samples of clinker discharged from the bottom of a pulverized coal-fired boiler, XRD measurements were performed in the 2θ=15-50° range. In each diffraction pattern obtained, the area of ​​the halo region above the line connecting the base points of 2θ=15° and 2θ=50° was defined as the amount of amorphous matter, and the sum of the areas of the diffraction peaks detected above the halo region was defined as the amount of crystalline matter. The ratio Y of the amount of amorphous matter to the sum of the amounts of amorphous matter and crystalline matter was defined as the area of ​​the halo region above the line connecting the base points of 2θ=15° and 2θ=50°. The method according to any one of the above [1] to [3], characterized in that a first-order approximation equation is obtained in advance from the relationship between the height X of the halo region at 2θ=25° and the height X of the halo region above the line connecting the base points of 2θ=15° and 2θ=50° in a diffraction pattern obtained by XRD measurement of the most recent bottom ash clinker discharged from the bottom of a pulverized coal combustion boiler, and the adhesion and growth property of the clinker is evaluated by calculating a value from the height X of the halo region at 2θ=25° above the line connecting the base points of 2θ=15° and 2θ=50° using the first-order approximation equation as the amorphous fraction of the most recent clinker.

[0020] [6] The method according to [4] or [5] above, characterized in that the type and mixing ratio of the solid fuels to be mixed and burned are adjusted so that the proportion of amorphous matter in the clinker discharged from the bottom of the pulverized coal-fired boiler exceeds 50%.

[0021] [7] A method according to any one of [1] to [6] above, characterized in that the amount of SiO2 contained in the clinker discharged from the bottom of a pulverized coal combustion boiler is compared with the amount of cristobalite in the clinker, and the type and mixing ratio of the solid fuel to be mixed and burned are adjusted so that the proportion of SiO2 contained in the clinker that has been converted to cristobalite does not exceed approximately 10%.

[0022] [8] The method according to the above item [7], characterized in that in a diffraction pattern obtained by subjecting clinker discharged from the bottom of a pulverized coal combustion boiler to XRD measurement in the region of 2θ=15 to 50°, the area of ​​a halo region above a line connecting the base points of 2θ=15° and 2θ=50° is defined as the amount of amorphous matter, the sum of the areas of diffraction peaks detected above the halo region is defined as the amount of crystalline matter, the proportion of cristobalite contained in the crystalline matter is calculated by the RIR method, the proportion of cristobalite is calculated by multiplying the amount of crystalline matter by the amount of crystalline matter, and the amount of cristobalite relative to the sum of the amount of amorphous matter and the amount of crystalline matter is defined as the proportion of cristobalite in the bottom ash clinker.

[0023] [9] Using multiple samples of clinker discharged from the furnace bottom of a pulverized coal-fired boiler, XRD measurements were performed in the 2θ=15-50° range. In each diffraction pattern obtained, the area of ​​the halo region above the line connecting the base points of 2θ=15° and 2θ=50° was defined as the amount of amorphous matter, and the sum of the areas of the diffraction peaks detected above the halo region was defined as the amount of crystalline matter. A linear approximation was obtained in advance from the relationship between the ratio Y of the amount of amorphous matter to the sum of the amount of amorphous matter and the amount of crystalline matter, and the height X of the halo region above the line connecting the base points of 2θ=15° and 2θ=50° at 2θ=25°. The XRD equation for the most recent clinker discharged from the furnace bottom of a pulverized coal-fired boiler was then calculated. The method according to the above item [7], characterized in that in the diffraction pattern obtained during the D measurement, a value calculated using the first-order approximation equation from the height at 2θ=25° in the halo region above the line connecting the base points of 2θ=15° and 2θ=50° is the proportion of amorphous material in the nearest bottom ash clinker, the sum of the areas of the diffraction peaks detected above the halo region is the amount of crystalline material, the proportion of cristobalite contained in the crystalline material is calculated using the RIR method, and the amount of cristobalite is determined by multiplying the proportion by the amount of crystalline material, and the amount of cristobalite relative to the sum of the amount of amorphous material and the amount of crystalline material is determined as the proportion of cristobalite in the bottom ash clinker.

[0024]

[10] The method according to any one of [1] to [9] above, wherein the solid fuel is coal and / or biomass solid fuel. Effect of the Invention

[0025] According to this embodiment, when solid fuels with different properties from conventional coal, such as biomass solid fuels, which are expected to become more widely used in the future, are used in existing pulverized coal-fired boilers, the tendency for clinker to adhere to the inside of the furnace, which hinders the stable operation of the pulverized coal-fired boiler, can be grasped in a timely manner and dealt with appropriately without shutting down the boiler. This makes it possible to avoid problems such as a large amount of clinker peeling off from the inside of the furnace, which would cause the boiler to shut down immediately, and to maintain stable operation of the boiler. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present invention will be described in detail below.

[0027] According to this embodiment, the ash composition expected when multiple solid fuels are mixed is compared and evaluated based on the ash content and composition of the ash in each solid fuel that have been analyzed in advance, with the composition of the bottom ash clinker discharged from the bottom of the boiler furnace when the multiple solid fuels are mixed, and the crystal state of the bottom ash clinker is analyzed to evaluate the adhesion status inside the clinker furnace, and the type and blending ratio of the solid fuels to be mixed are adjusted, thereby suppressing the adhesion and growth of clinker inside the furnace when multiple types of solid fuels are mixed in a pulverized coal combustion boiler.

[0028] When coal used as fuel for pulverized coal-fired boilers arrives, its various qualities (for example, industrial analysis values ​​for moisture, volatile matter, ash content, calorific value, etc., elemental analysis for nitrogen content and total sulfur, etc., various quality analysis results such as the composition of ash after incineration, etc.) are reported by the shipper based on analysis methods stipulated in industrial standards such as ISO, ASTM, JIS, etc. Biomass solid fuels are also analyzed for the same analysis items as coal using the same analysis methods as coal, and the results are reported by the shipper. For construction waste and other materials that do not receive the same analysis items as coal from their source, a voluntary analysis is conducted in advance using the same analysis methods as coal.

[0029] Based on the analysis results reported by the shipper of each solid fuel to be mixed and burned in a pulverized coal combustion boiler or the results of independent analysis, the ash composition expected during mixed combustion can be estimated from the ash content of each solid fuel, the composition of that ash, and the blending ratio of multiple solid fuels to be mixed.

[0030] According to this embodiment, the pulverized coal combustion boiler has various device structures, but generally has a plurality of burners and a plurality of air supply nozzles in the furnace. The pulverized solid fuel is air-transported to the burner, ignited at the burner outlet, and gradually progresses in combustion until complete combustion occurs while mixing with the airflow from the air nozzle. Fly ash is generated, and the hot flame blast from the combustion heats the evaporator tubes arranged throughout the boiler. Some of the fly ash generated in the hot flame blast adheres to the burner periphery and the evaporator tube surface in the furnace as clinker. When the clinker adheres to the burner periphery and the evaporator tube surface in the furnace accumulates to a certain extent, it peels off from the adhesion surface and falls into a water-sealed ash basin at the bottom of the boiler furnace, where it is cooled and discharged to the outside of the furnace as bottom ash clinker.

[0031] The surface temperature of the clinker adhering to the burner periphery is about 1100-1300°C, and it is assumed that the adhesion and growth of clinker occurs in this temperature range. When a pulverized coal-fired boiler is operating stably, the adhesion and growth of clinker inside the furnace is balanced with the separation and fall, and the adhesion and growth of clinker inside the furnace does not progress, but if this balance is lost, the adhesion and growth of clinker inside the furnace progresses, and it becomes impossible to continue operating the boiler unless an external impact is applied to cause the adhering clinker to separate and fall from the inner furnace wall repeatedly before problems occur due to large amounts of separation.

[0032] Therefore, the inventors have found that in order to suppress the adhesion and growth of clinker, it is important to evaluate the adhesion clinker actually generated in the furnace and to control the ash component and the clinker generation temperature. That is, by collecting and analyzing the bottom ash clinker discharged from the bottom of the boiler furnace, it is possible to evaluate the adhesion and growth of clinker in the furnace, and by taking measures to adjust the ash component and the clinker generation temperature, it is possible to mitigate the adhesion and growth of clinker in the furnace and maintain stable and continuous operation of the pulverized coal combustion boiler. More specifically, by collecting the bottom ash clinker discharged from the bottom of the boiler furnace and analyzing its composition, and grasping the type of crystalline matter contained in the clinker and the ratio of amorphous matter to crystalline matter, the blending ratio of the fuels to be mixed and burned is adjusted, the calorific value of the mixed fuel and the ash component composition that will be generated after combustion are adjusted, and in some cases, the clinker generation temperature is adjusted, including the adjustment of the temperature distribution in the furnace by changing the amount of air supplied to the furnace and its distribution, and measures are taken to reduce the amount of crystals generated in the clinker.

[0033] The composition of bottom ash clinker can be easily analyzed using XRF (X-ray fluorescence analysis), a method known for analyzing the composition of solids.

[0034] According to this embodiment, the analysis of clinker by XRF is carried out by crushing a sample in an agate mortar and forming it into tablets, and measuring it using an energy dispersive X-ray fluorescence device, for example, S2PUMA manufactured by Bruker, under the conditions of a tube: Pd and a tube voltage of 20 to 50 kV, and quantitative calculation is carried out by the fundamental parameter method (FP method) using software attached to the device, with the detected elements considered as oxides.

[0035] In general, the composition of bottom ash clinker tends to be slightly higher in heavy components such as Fe2O3 and CaO compared to fly ash, but the difference is slight, and the two are almost the same. Therefore, if the composition of the ash expected when multiple solid fuels are mixed and the composition of the bottom ash clinker discharged from the bottom of the boiler furnace are almost the same, it can be confirmed that the analyzed bottom ash clinker is clinker generated as a result of the combustion of the fuel used. Then, an analysis is performed using XRD (X-ray diffraction) to determine the type of crystalline matter contained in the clinker and the ratio of amorphous to crystalline matter.

[0036] According to this embodiment, the analysis of clinker by XRD is performed by crushing a sample in an agate mortar and then using a powder X-ray diffractometer, for example, X'Pert Pro MPD manufactured by Spectris, under the conditions of tube: Cu (Kα), tube current: 40 mA, tube voltage: 45 kV, sampling width: 0.0167° / step, integration time: 100 sec. / step, and measurement range (2θ): 5 to 80°, and analyzing in the range of 2θ=15 to 50° where the diffraction peaks of the main crystals contained in the clinker exist. In the analysis, the area of ​​the halo region above the straight line connecting the base points of 2θ=15° and 2θ=50° is regarded as the amount of amorphous matter, and the sum of the areas of the diffraction peaks detected above the halo region is regarded as the amount of crystalline matter.

[0037] There are various known methods for calculating the proportion of each component contained in the crystalline material. For example, the RIR method, which simply calculates a quantitative value using the intensity of the maximum line of the test component and a reference intensity ratio (RIR value) stored in a database, is preferable because it can calculate a quantitative value without creating a calibration curve and therefore does not require complicated sample preparation or measurement.

[0038] FIG. 1 shows an example of XRD analysis in this embodiment. In each diffraction pattern obtained by XRD measurement in the region of 2θ=15 to 50° for a plurality of samples of bottom ash clinker discharged from the bottom of the boiler furnace, the area of ​​the halo region above the straight line connecting the base points of 2θ=15° and 2θ=50° is defined as the amount of amorphous matter, and the sum of the areas of the diffraction peaks detected above the halo region is defined as the amount of crystalline matter.

[0039] Next, a method for calculating the amorphous content in the bottom ash clinker in this embodiment will be described with reference to Fig. 2. A linear approximation formula is derived in advance from the relationship between the ratio of the amount of amorphous to the sum of the amount of amorphous and the amount of crystalline in the bottom ash clinker obtained by XRD analysis (Y axis) and the height of 2θ=25° in the halo region above the straight line connecting the base points of 2θ=15° and 2θ=50° (X axis), and the value calculated from the linear approximation formula from the height of 2θ=25° in the halo region above the straight line connecting the base points of 2θ=15° and 2θ=50° in the diffraction pattern obtained when the most recent bottom ash clinker discharged from the furnace bottom of the boiler is measured by XRD can be regarded as the amorphous content of the most recent bottom ash clinker, and the amount of amorphous can be grasped more easily.

[0040] Furthermore, by calculating the proportion of each component contained in the crystalline material using the RIR method or the like, it is possible to calculate the proportion of a specific crystal relative to the whole, taking into account the proportion of amorphous material.

[0041] When the amount of crystalline matter in the clinker increases and the amount of amorphous matter decreases, the adhesion of clinker to the inside of the boiler progresses, so it is preferable to increase the amount of amorphous matter. In particular, when the amount of amorphous matter falls below 50%, the tendency for clinker to adhere increases. The reason for this is presumably that amorphous matter has a low melting point and changes state when the temperature changes, making it easy to peel off, whereas crystalline matter with a high melting point does not change state once it is formed, and it becomes solid and difficult to peel off.

[0042] As for the crystalline substances present in the clinker, quartz and cristobalite are detected from the SiO2 content, mullite from the Al2O3 content, anorthite when the CaO content is high, and cordierite when the MgO content is high. The reason for the increase in these crystalline substances is presumed to be related to the melting points and transition temperatures of these crystals. That is, the melting points of mullite are 1850°C, anorthite is 1550°C, and cordierite is 1450°C, and these temperatures are considerably higher than the surface temperature of the clinker attached around the burner, which is 1100-1300°C, so it is presumed that these crystals once formed do not return to amorphous, but rather adhere and grow without peeling off.

[0043] In addition, the crystal transformation of SiO2 with respect to temperature is alpha quartz (573°C) → beta quartz (867°C) → tridymite (1470°C) → cristobalite (1713°C) → quartz glass. Therefore, it can be inferred that the higher the amount of silica carried by the fuel that is converted to cristobalite, the higher the temperature inside the furnace, which is thought to promote the formation of the above crystals.

[0044] According to this embodiment, when the amount of SiO2 contained in the bottom ash clinker is compared with the amount of cristobalite in the bottom ash clinker, and the proportion of SiO2 in the bottom ash clinker that is equivalent to the SiO2 content brought in by the fuel that has been converted to cristobalite exceeds approximately 10%, the adhesion and growth of clinker in the furnace tends to be promoted. [Brief description of the drawings]

[0045] [Figure 1] This is an example of analysis of a diffraction pattern for calculating the amount and ratio of amorphous and crystalline matter in the bottom ash clinker by XRD measurement of the bottom ash clinker in the present invention. [Diagram 2] 2 is a graph showing an example of a linear approximation formula for calculating the proportion of amorphous matter in bottom ash clinker in the present invention. EXAMPLES

[0046] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. In these examples, XRF analysis and XRD analysis of clinker were performed as follows. The proportions of each component contained in the crystalline matter of the clinker were determined by the RIR method.

[0047] [XRF analysis of clinker] The clinker samples were crushed in an agate mortar and then formed into tablets. Measurements were performed using an energy dispersive X-ray fluorescence spectrometer (Bruker S2PUMA) with a Pd tube and a tube voltage of 20 to 50 kV. Quantitative calculations were performed using the fundamental parameter method (FP method) with the detected elements considered as oxides using the software provided with the device.

[0048] [XRD analysis of clinker] The clinker sample was ground in an agate mortar and then measured using a powder X-ray diffractometer (Spectris X'Pert Pro MPD) under the following conditions: tube: Cu (Kα), tube current: 40 mA, tube voltage: 45 kV, sampling width: 0.0167° / step, accumulation time: 100 sec. / step, measurement range (2θ): 5 to 80°.

[0049] Next, in the range of 2θ=15 to 50° where the diffraction peaks of the main crystals contained in the clinker exist, the area of ​​the halo region above the line connecting the base points of 2θ=15° and 2θ=50° was defined as the amount of amorphous matter, and the sum of the areas of the diffraction peaks detected above the halo region was defined as the amount of crystalline matter, thereby determining the amorphous proportion in the clinker sample.

[0050] [Example 1] In order to generate steam and generate electricity in a pulverized coal-fired boiler at a coal-fired power plant, fuel A (normal coal produced in Australia) and fuel B (normal coal produced in Indonesia) in a weight ratio of 40:60 were fed into a pulverizer and pulverized, and then combusted in a pulverized coal-fired boiler. When the inside of the furnace was observed, it was found that the adhesion of clinker to the furnace wall had progressed to some extent. The composition of the bottom ash clinker recovered from the bottom of the boiler was analyzed by XRF and the crystal state by XRD. The weighted average ash composition assumed when fuel A and fuel B are mixed and burned in a ratio of 40:60 based on the ash composition of each fuel was almost the same as the XRF analysis value of the bottom ash clinker, and it was inferred that the bottom ash clinker recovered from the bottom of the boiler was generated by the mixed combustion of fuel A and fuel B. The amorphous ratio of the bottom ash clinker at this time was 52%, mullite was 19%, anorthite was 18%, and cordierite was 6%. In addition, the percentage of SiO2 in the bottom ash clinker that was converted to cristobalite was 4%, which corresponds to the SiO2 content contained in the fuel.

[0051] Fuel B was replaced with fuel C, which has a lower calorific value, and the fuel was pulverized by feeding it into a pulverizer without changing the feeding ratio of 40:60, and similarly combusted in a pulverized coal-fired boiler. When the inside of the furnace was observed, it was confirmed that the progress of clinker adhesion to the furnace wall had slowed down, and the bottom ash clinker recovered from the bottom of the boiler was analyzed for composition by XRF and crystal state by XRD. The weighted average ash composition assumed when fuel A and fuel C are mixed and fired at a ratio of 40:60 based on the ash composition of each fuel was almost the same as the XRF analysis value of the bottom ash clinker, and it was inferred that the bottom ash clinker recovered from the bottom of the boiler was generated by the mixed firing of fuel A and fuel C. The amorphous ratio of the bottom ash clinker at this time increased to 71%, and mullite decreased to 15%, anorthite to 0%, and cordierite to 4%. In addition, the percentage of SiO2 in the bottom ash clinker that was converted to cristobalite was 6%, which corresponds to the SiO2 content contained in the fuel.

[0052] The combustion results of Example 1 are shown in Tables 1 and 2. It can be seen that the progression of clinker adhesion was mitigated by adjusting the fuel blending.

[0053] [Table 1]

[0054] [Table 2]

[0055] [Example 2] As in Example 1, fuel D (construction waste), fuel E (Australian coal), and fuel F (Indonesian coal) in Table 2 were fed into a pulverizer in a weight ratio of 3:38:58, pulverized, and combusted in a pulverized coal-fired boiler. When the inside of the furnace was observed, it was found that the adhesion of clinker to the furnace wall had progressed significantly, so the adhering clinker was peeled off and dropped using a metal rod through the observation window of the boiler. When the composition of the bottom ash clinker recovered from the bottom of the boiler was analyzed by XRF and the crystal state by XRD, the weighted average ash composition assumed when fuel D, fuel E, and fuel F were mixed and burned in a ratio of 3:38:58 based on the ash composition of each fuel was almost the same as the XRF analysis value of the bottom ash clinker, and it was inferred that the bottom ash clinker recovered from the bottom of the boiler was generated by the mixed combustion of fuel D, fuel E, and fuel F. The amorphous content of the bottom ash clinker at this time was 46%, mullite 11%, anorthite 31%, and cordierite 6%. In addition, the percentage of SiO2 in the bottom ash clinker that was equivalent to the SiO2 content contained in the fuel that was converted to cristobalite was 5%.

[0056] Fuel F was replaced with fuel G (low-grade coal produced in Indonesia) with a lower calorific value, and the ratio was changed to 3:49:49. The fuel was then fed into a pulverizer and pulverized, and was then burned in a pulverized coal-fired boiler. Observation of the inside of the furnace confirmed that the progress of clinker adhesion to the furnace wall had slowed. The composition of the bottom ash clinker recovered from the bottom of the boiler was analyzed by XRF and the crystal state by XRD. The weighted average ash composition assumed when fuel D, fuel E, and fuel G were mixed in a ratio of 3:49:49 based on the ash composition of each fuel was almost the same as the XRF analysis value of the bottom ash clinker. It was inferred that the bottom ash clinker recovered from the bottom of the boiler was generated by the mixed combustion of fuel D, fuel E, and fuel G. The amorphous ratio of the bottom ash clinker at this time increased to 63%, mullite increased to 17%, anorthite decreased to 0%, and cordierite increased to 16%. In addition, the percentage of SiO2 in the bottom ash clinker that was converted to cristobalite was 4%, which corresponds to the SiO2 content contained in the fuel.

[0057] The combustion results of Example 2 are shown in Tables 3 and 4. It can be seen that the progression of clinker adhesion was mitigated by adjusting the fuel blending.

[0058] [Table 3]

[0059] [Table 4]

[0060] [Example 3] As in Examples 1 and 2, fuel C, fuel H (normal coal produced in Australia), and fuel I (normal coal produced in Indonesia) in Table 3 were fed into a pulverizer in a weight ratio of 3:58:38, pulverized, and combusted in a pulverized coal-fired boiler. When the inside of the furnace was observed, the adhesion of clinker to the furnace wall was slight and stable. When the composition of the bottom ash clinker recovered from the bottom of the boiler was analyzed by XRF and the crystal state by XRD, the weighted average ash composition assumed when fuel C, fuel H, and fuel I were mixed and burned in a ratio of 3:58:38 based on the ash composition of each fuel was almost the same as the XRF analysis value of the bottom ash clinker, and it was inferred that the bottom ash clinker recovered from the bottom of the boiler was generated by the mixed combustion of fuel C, fuel H, and fuel I. The amorphous ratio of the bottom ash clinker at this time was 69%, and mullite was 19%. In addition, the percentage of SiO2 in the bottom ash clinker that was converted to cristobalite was 5%, which corresponds to the SiO2 content contained in the fuel.

[0061] Fuel H was replaced with fuel J (normal coal produced in Australia) from the same region, which has almost the same characteristics, and fuel I was replaced with fuel K (normal coal produced in Indonesia), which is slightly lower quality but has a high calorific value from the same region. The ratio of fuels was also changed to 3:38:58, and the fuels were fed into a pulverizer to be pulverized, and then combusted in a pulverized coal-fired boiler. When the inside of the furnace was observed, the progress of clinker adhesion to the furnace wall increased, so the clinker was peeled off and dropped from the observation window of the boiler using a metal rod. The composition of the bottom ash clinker recovered from the bottom of the boiler was analyzed by XRF and the crystal state by XRD. The weighted average ash composition assumed when fuels C, J, and K were co-fired in a ratio of 3:38:58 based on the ash composition of each fuel was almost the same as the XRF analysis value of the bottom ash clinker, and it was inferred that the bottom ash clinker recovered from the bottom of the boiler was generated by co-firing fuels C, J, and K. At this time, the amorphous ratio of the bottom ash clinker decreased to 52%, mullite increased to 20%, and plagioclase was formed at 12%. Also, the ratio of cristobalite to the SiO2 content in the bottom ash clinker, which corresponds to the SiO2 content contained in the fuel, increased to 12%.

[0062] Fuel L (Australian normal coal) and fuel M (black pellets) were added as new fuels, and the ratio of fuel C, fuel J, fuel K, fuel L, and fuel M was 3:29:44:19:5. The mixture was then fed into multiple pulverizers to be pulverized, and burned in a pulverized coal-fired boiler. Observation of the adhesion of clinker to the inner wall of the furnace confirmed a decrease in the overall calorific value and a tendency for the progress of clinker adhesion to the furnace wall to slow down. The composition of the bottom ash clinker recovered from the bottom of the boiler was analyzed by XRF and the crystal state by XRD. The weighted average ash composition assumed when fuel C, fuel J, fuel K, fuel L, and fuel M were mixed in a ratio of 3:29:44:19:5 based on the ash composition of each fuel was almost the same as the XRF analysis value of the bottom ash clinker. It was therefore inferred that the bottom ash clinker recovered from the bottom of the boiler was generated by the mixed combustion of fuel C, fuel J, fuel K, fuel L, and fuel M. The amorphous fraction of the bottom ash clinker at this time increased to 69%, mullite decreased to 17%, and plagioclase decreased to 2%. In addition, the fraction of SiO2 in the bottom ash clinker that was equivalent to the SiO2 contained in the fuel that was converted to cristobalite decreased to 10%.

[0063] The combustion results of Example 3 are shown in Tables 5 to 7. It can be seen that the adhesion of clinker progressed by adjusting the fuel blending, but the progress of the clinker adhesion was mitigated by further adjusting the fuel blending.

[0064] [Table 5]

[0065] [Table 6]

[0066] [Table 7]

Claims

1. A method for suppressing the deposition and growth of clinker in a boiler furnace, when multiple types of solid fuels are burned in a pulverized coal-fired boiler, involves analyzing the crystal state of the clinker discharged from the bottom of the boiler, evaluating the deposition and growth tendency of the clinker, and then adjusting the types and mixing ratio of the solid fuels to be mixed and burned.

2. 2. The method according to claim 1, wherein the clinker discharged from the bottom of a pulverized coal-fired boiler furnace is clinker that has peeled off and fallen from an inner wall of the boiler furnace.

3. 2. The method according to claim 1, characterized in that the clinker discharged from the bottom of a pulverized coal-fired boiler furnace is peeled off from the inner wall of the boiler furnace by applying an external impact and dropped to the bottom of the boiler furnace.

4. The method according to claim 1, characterized in that, in a diffraction pattern obtained by XRD measurement of clinker discharged from the furnace bottom of a pulverized coal combustion boiler in the region of 2θ = 15 to 50°, the area of ​​the halo region above the straight line connecting the base points of 2θ = 15° and 2θ = 50° is defined as the amount of amorphous matter, and the sum of the areas of the diffraction peaks detected above the halo region is defined as the amount of crystalline matter, and the ratio of the amount of amorphous matter to the sum of the amount of amorphous matter and the amount of crystalline matter is defined as the amorphous proportion of the clinker.

5. Using a plurality of samples of clinker discharged from the furnace bottom of a pulverized coal combustion boiler, XRD measurements were performed in the region of 2θ=15 to 50°, and in each diffraction pattern obtained, the area of ​​the halo region above the line connecting the base points of 2θ=15° and 2θ=50° was defined as the amount of amorphous matter, and the sum of the areas of the diffraction peaks detected above the halo region was defined as the amount of crystalline matter. The ratio Y of the amount of amorphous matter to the sum of the amount of amorphous matter and the amount of crystalline matter was determined, and the ratio Y of the amount of amorphous matter to the sum of the amounts of crystalline matter was determined, and the ratio Y of the amount of amorphous matter to the sum of the areas of the crystalline matter The method according to claim 1, characterized in that a first-order approximation equation is obtained in advance from the relationship of the height X of the halo region above 2θ=25°, and in a diffraction pattern obtained when XRD is measured for the most recent bottom ash clinker discharged from the bottom of a pulverized coal combustion boiler, the value calculated from the height X of the halo region above 2θ=25° above the straight line connecting the base points of 2θ=15° and 2θ=50° using the first-order approximation equation is used as the amorphous fraction of the most recent clinker, thereby evaluating the adhesion and growth property of the clinker.

6. 6. The method according to claim 4 or 5, characterized in that the types and mixing ratio of solid fuels to be mixed and burned are adjusted so that the ratio of amorphous matter in the clinker discharged from the furnace bottom of the pulverized coal combustion boiler exceeds 50%.

7. SiO contained in clinker discharged from the bottom of a pulverized coal-fired boiler 2 The amount of SiO contained in the clinker is compared with the amount of cristobalite in the clinker. 2 2. The method according to claim 1, wherein the types and mixing ratio of the solid fuels to be mixed and burned are adjusted so that the ratio of the converted cristobalite does not exceed approximately 10%.

8. 8. The method according to claim 7, wherein, in a diffraction pattern obtained by XRD measurement of clinker discharged from the furnace bottom of a pulverized coal combustion boiler in the region of 2θ = 15 to 50°, the area of ​​a halo region above a line connecting base points of 2θ = 15° and 2θ = 50° is defined as the amount of amorphous matter, the sum of the areas of diffraction peaks detected above the halo region is defined as the amount of crystalline matter, the abundance ratio of cristobalite contained in the crystalline matter is calculated by the RIR method, and the amount of cristobalite is determined by multiplying the abundance ratio by the amount of crystalline matter, and the amount of cristobalite relative to the sum of the amount of amorphous matter and the amount of crystalline matter is defined as the proportion of cristobalite in the bottom ash clinker.

9. A first-order approximation formula was obtained in advance from the relationship between the ratio Y of the amount of amorphous to the sum of the amount of amorphous and the amount of crystalline, where the area of ​​the halo region above the line connecting the base points of 2θ=15° and 2θ=50° is the amount of amorphous, and the sum of the areas of the diffraction peaks detected above the halo region is the amount of crystalline, and the height X of the halo region above the line connecting the base points of 2θ=15° and 2θ=50° at 2θ=25°. The XRD of the clinker most recently discharged from the furnace bottom of the pulverized coal-fired boiler was then calculated.

8. The method according to claim 7, further comprising the steps of: calculating a value calculated from the height at 2θ=25° in a halo region above a straight line connecting base points at 2θ=15° and 2θ=50° in a diffraction pattern obtained by the measurement using the linear approximation equation as the proportion of amorphous matter in the nearest bottom ash clinker; determining the amount of crystalline matter by the sum of areas of diffraction peaks detected above the halo region; calculating the proportion of cristobalite contained in the crystalline matter using the RIR method; multiplying the proportion by the amount of crystalline matter to determine the amount of cristobalite; and determining the amount of cristobalite relative to the sum of the amount of amorphous matter and the amount of crystalline matter as the proportion of cristobalite in the bottom ash clinker.

10. 2. The method according to claim 1, characterized in that the solid fuel is coal and / or biomass solid fuel.

Citation Information

Patent Citations

  • Method for predicting / evaluating adhesion of coal ash, and method for preventing adhesion of coal ash

    JP2004361368A

  • Boiler operation method and boiler equipment

    JP2017190908A